2022
DOI: 10.1080/0020739x.2022.2058429
|View full text |Cite
|
Sign up to set email alerts
|

Generalization strategies and representations used by final-year elementary school students

Abstract: Recent research has highlighted the role of functional relationships in introducing elementary school students to algebraic thinking. This functional approach is here considered to study essential components of algebraic thinking such as generalization and its representation, and also the strategies used by students and their connection with generalization. This paper jointly describes the strategies and representations of generalisation used by a group of 33 sixth-year elementary school students, with no form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
1
0
4
Order By: Relevance
“…Multiple representation was present as the combination of verbal and pictorial, verbal and symbolic and even verbal, symbolic and pictorial. This study, like others, shows that high-performing students of these ages have the potential to use different representations and to handle algebraic symbolism (Akkan, 2013;Ureña et al, 2022). These findings are consistent with results reported by Cañadas & Fuentes (2015), who observed that verbal and symbolic representation are the two types most frequently used, along with a combination of these two and even all three types.…”
Section: Representationsupporting
confidence: 92%
See 1 more Smart Citation
“…Multiple representation was present as the combination of verbal and pictorial, verbal and symbolic and even verbal, symbolic and pictorial. This study, like others, shows that high-performing students of these ages have the potential to use different representations and to handle algebraic symbolism (Akkan, 2013;Ureña et al, 2022). These findings are consistent with results reported by Cañadas & Fuentes (2015), who observed that verbal and symbolic representation are the two types most frequently used, along with a combination of these two and even all three types.…”
Section: Representationsupporting
confidence: 92%
“…In contrast, more-highly performing seventh-and eighth-graders generalized using a variety of representations, including algebraic symbolism. Also, in research involving 33 sixth-graders solving a problem with area calculations, students were able to generalize verbally as well as symbolically, showing a clear preference for a functional approach (Ureña et al, 2022). Moving up a level, middle-school students can represent relationships with variable notation including linear relationships and quadratic relationships (e.g., Ellis 2011a;Francisco & Hähkiöniemi, 2012).…”
Section: Structuresmentioning
confidence: 99%
“…Este fue un experimento de enseñanza de Blanton y Kaput (2004), se les planteó encontrar la relación entre las colas y ojos de un grupo de perros, los alumnos más pequeños (3-4 años) contaron los elementos concretos que fueron relacionando en una tabla, en cambio los alumnos más grandes (5 años) lograron encontrar un patrón con el cual generalizar. Ya en último curso de primaria (11-12 años), encontramos una investigación que relaciona las estrategias y representaciones de un grupo de 33 alumnos, se les plantearon dos situaciones de generalización, las estrategias utilizadas en los casos específicos fue el conteo directo, a medida que los valores aumentaban llevándolos a la generalización diversificaron sus estrategias, utilizando primordialmente la de covariación, los alumnos lograron generalizar verbal y simbólicamente (Ureña et al, 2022).…”
Section: Representacionesunclassified
“…La primera requiere la activación de algunas componentes del sentido espacial y la generalización, siendo esta última el enfoque y fin último de la tarea; mientras que la última se centra específicamente en la activación de las habilidades de visualización, por lo que permite un análisis más profundo de estas. Varias investigaciones han abordado las cualidades de estas tareas para determinar el papel de las habilidades de visualización y la generalización en la identificación del talento matemático (Aznarte, 2018;Ureña et al, 2022). Aznarte (2018) analizó las componentes del sentido espacial que se ponen en juego al resolver estas dos tareas y encuentra que en general los estudiantes tienen un mejor desempeño en preguntas que no requieren la activación de las componentes del sentido espacial y que al comparar los resultados obtenidos por los alumnos que fueron seleccionados como alumnos con talento matemático evidenciaron un mayor rendimiento en las tareas analizadas, siendo notorio de manera particular en los problemas que implican el sentido espacial.…”
Section: Instrumentounclassified
“…Para la obtención de resultados, se dispone del análisis de la prueba original (Aznarte, 2018;Ureña et al, 2022) y de la resolución de la prueba adaptada por parte de la persona ciega descrita anteriormente. Dicha resolución fue presentada por la participante de manera digital, atendiendo a la forma en que fueron presentadas las tareas en su versión modificada.…”
Section: B) Versión Modificadaunclassified